Agrobank contributes pocket money to 35 selected undergraduates - UMP, PNC (2019)
A total of 35 Universiti Malaysia Pahang (UMP) students received assistances included pocket money totalling RM17,500 under the UMP MyGift programme called ‘Pocket Money Initiative’ that was aimed to lessen their financial burden. The money was from tithesprovided by Agrobank which also contributed takaful aids amounting to RM385,000 that served as Personal and Accident Protection Scheme to the students who were from the B40 family background. Pahang Agrobank Director, Safaruddin Samsuddin presented the aids to UMP Vice-Chancellor, Professor Dato’ Sri. Dr.Daing Nasir Ibrahim at the Banquet Hall, Tun Abdul Razak Chancellery in Pekan UMP on April 29, 2019.